Who Was He? Internment, Exile and Ambiguity in Norbert Gstrein’s Novel Die englischen Jahre (The English Years) (1999) - Martin Löschnigg (Institute of English Studies, 2021)
Winner of the Alfred Döblin Preis in 1999, the novel Die englischen Jahre by the Austrian novelist Norbert Gstrein deals with internment and exile in Britain during and after the Second World War. It centres on the (fictitious) character of Gabriel Hirschfelder, a writer and refugee from Nazi-occupied Austria who is detained, with other ‘enemy aliens,’ in a camp on the Isle of Man. There, Nazi sympathisers are interned together with Jewish and political refugees, and the central chapters in the novel depict the conditions and resulting conflicts in the internment camp. Hirschfelder dies in exile at Southend-on-Sea, having confessed shortly before his death that he killed a fellow inmate. This confession as well as reports of a transport of internees sunk off the coast of Scotland in 1940 incite a young Austrian woman to try to solve the mystery surrounding Hirschfelder and his allegedly lost autobiography The English Years. The paper discusses how Gstrein combines different genres like the historical novel/historiographic metafiction and the whodunit as well as using multiple narrative perspectives and refractions to pinpoint questions of shifting identities and allegiances, and of belonging and alienation in the wake of internment and exile.